High-Performance Thermoelectricity in Ferrocene Molecular Wires - Rasha Talal Jasem; Mohammed Deia Noori (University of Thi-Qar Journal of Science, 2025)
The transport characteristics of the ferrocene trimer molecule and its reaction to temperature changes were investigated theoretically Here, we have conducted a theoretical comparison of the thermoelectric and electrical characteristics of four distinct ferrocene trimer topologies. Our findings show that the bonding type and connectivity between ferrocene trimer units significantly affect the regulation of quantum interference (QI) and the enhancement of thermoelectric characteristics indicating that these structures are excellent candidates to serve as materials for numerous thermoelectric applications and as thermoelectric enhancers such as Cooling/heating, power generation, and heat flux sensors.